Integrated mobile zakat Melaka using rule based / Ahmad Zakwan Azizan - Azizan, Ahmad Zakwan (Faculty of Computer and Mathematical Sciences, 2017)
Zakat is the one of the five pillars of Islam, every Muslims must ensure that they will pay the zakat if affordable. Zakat is a mean of fulfilling social responsibility and is an obligation to Muslims for those who have excess wealth of basic needs to give a specific amount of their riches to payees of zakat that meet certain conditions and requirement. Zakat is the pivot approach in Islamic teachings to encounter social problem such as poverty in society by sharing the percentage of wealth to relevant recipients as the obligation to the person who affordable. The traditional system using web-based system. Nowadays, people prefer to use mobile application have become an integral part of daily lives of million people in the world using smartphones or tablets. Therefore, an increasing number of user forcing the developer to develop the mobile application using rule-based technique. One of the mobile application was developed is Integrated mobile zakat Melaka using mobile application that focus in Melaka state. There are seven types of zakat can be calculated through this mobile application. This system will increase the awareness of zakat payment and collection of zakat. Besides that, the value of the zakat nisab already set in the system. The significance of the system easy to used, efficient, usability, fast result and user friendly.